0629 Feasibility of Observed but Physically Unaided Continuous Positive Airway Pressure Set Ups. (27th May 2020) - Hevener, W; Barnes, F; Munafo, D A
Abstract: Introduction: We sought to determine if an observed but physically unaided CPAP set up, utilizing only a detailed set of CPAP instructions without direct involvement of a Respiratory Therapist, could yield similar Medicare compliance rates when compared to the conventional method of hands-on instruction. Methods: This was a single center, prospective trial. All patients were CPAP naïve. A total of 393 patients completed the physically unaided set ups utilizing a starter kit designed by Resmed (Airsense 10 Autoset, instructions and 3 mask options, P10, N20, F20). Patients were asked to set themselves up under observation with only verbal assistance provided if requested. No patient required conversion to conventional set up. 5287 completed the conventional set ups. We compared the success of observed but unaided CPAP set ups to the success rate for conventional CPAP set ups performed with physical assistance. The primary success endpoint was Medicare compliance within 90 days. Results: The two groups were not significantly different with regard to gender, age, baseline AHI, and initial mask selection. The Medicare compliance of the unaided set ups was not significantly different from the conventional set ups (75% vs. 77% respectively, p=NS). Similarly, adherence at ten days (65% vs. 69%, p=NS) and thirty days (65% vs. 68%, p=NS) was no different between the two groups and the percentage of mask re-fits required at ten and thirty days was similarly no different. Conclusion: We conclude that for the CPAP equipment used, observed but physically unaided CPAP set ups can yield similar Medicare compliance rates when compared to physically aided CPAP set ups. Further, we speculate that because these techniques yielded similar success rates the principal factor determining ultimate success is patient follow up and support once therapy is initiated. Support: None.